Environmental Preservation and Water Pollution from the Islamic Perspective - Mohamad, Abdul Basir; Ismail, Nurbazla (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Islam is a religion of peace, security, and prosperity for all beings in our surroundings. This paper aims to discuss environmental and water pollution according to Islamic views. The study of environmental protection, environmental control, preservation, and balance of nature is something that is urgent from an Islamic point of view. This research is qualitative research that obtains data from primary and secondary sources, namely books, articles, journals, and papers. Data were analyzed inductively, deductively, and comparatively regarding Islamic sources and environmental science. After that, all data was collected and recorded descriptively. This study concludes that Islamic law strictly prohibits all actions that can damage and destroy the environment. The environment must be maintained and monitored as best as possible from the occurrence of something that can damage it. The term damage is often repeated by Allah SWT in the Qur'an to show that it is something that is important to understand and must be fully paid attention to in order to ensure environmental sustainability. Environmental damage comes from human actions that clearly damage this earth and human beings themselves. Human behavior is usually influenced by desire regardless of the consequences for the environment. The research also argues that Islamic law is very concerned about protecting the environment and prohibits strict environmental encroachment and if there are parties who pollute air resources, they can be prosecuted. This paper contributes to environmental preservation according to the Islamic perspective.